Perlawanan terhadap tradisi dalam novel tenggelamnya kapal Van Der Wijck: Tinjauan teori poskolonial : Resistance to Tradition in the Novel Tenggelamnya Kapal Van Der Wijck: A Review of Postcolonial Theory - Musriyah, Musriyah; Wibowo, Moh. Ari (Information Technology and Science(ITScience), 2025)
Below is the OJS-style academic English translation of your text. The tone is formal, concise, and suitable for a journal article. The novel Tenggelamnya Kapal Van der Wijck by Hamka not only presents a tragic love story but also reflects the tension between rigid Minangkabau customary norms and the individual aspirations emerging within a society in transition. Tradition, when preserved in an inflexible manner, often generates identity conflicts and suppresses personal freedom, making the text particularly compelling when examined through a postcolonial lens. This study employs a qualitative method with a descriptive–interpretative approach. Data were collected through close reading and note-taking techniques, then analyzed using key concepts in postcolonial theory such as hybridity, subalternity, and mimicry. The validity of the data was strengthened through theory, source, and researcher triangulation. The analysis reveals three major forms of resistance to tradition within the novel. First, Zainuddin’s proactive resistance is manifested through the construction of a hybrid identity positioned outside the hegemony of customary norms. Second, Hayati’s passive resistance represents the voice of the subaltern within patriarchal structures. Third, Aziz’s destructive resistance emerges through his mimicry of Western modernity, which ultimately leads to self-ruin. These three modes of resistance indicate that tradition can operate as a form of internal colonialism that constrains the individual. The study concludes that Tenggelamnya Kapal Van der Wijck is not merely a romantic narrative but also serves as a counter-narrative critiquing oppressive customs and power structures. Thus, Hamka’s work can be understood as a reflection of identity struggles and resistance against cultural hegemony within a postcolonial context.